(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
This paper analyses the problem and designs the supply chain management for perishable products. The challenges for managing these products in that: their value deteriorates over time in the supply at the rates that are highly temperature and humidity dependent. Mismanagement supply chain destroys these products.